2003
DOI: 10.4049/jimmunol.170.8.4045
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Activin A Expression in Mast Cells and Asthma: Its Effect on the Proliferation of Human Airway Smooth Muscle Cells

Abstract: Activin A, a homodimeric protein (βAβA) and a member of the TGF-β superfamily, is involved in the inflammatory repair process. Using cDNA microarray analysis, we discovered strong induction of the activin βA gene in human mast cells (MC) on stimulation with PMA and calcium ionophore (A23187). Activin βA mRNA was also highly induced in primary cultured murine bone marrow MC (BMMC) after stimulation by IgE receptor cross-linking. Secretion of activin A was evident in human mast cell-1 line cells 3 h after stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 49 publications
6
85
0
1
Order By: Relevance
“…Similar to other cytokines, activin A appears to be secreted in a second wave of mediators by mast cells, thus requiring de novo synthesis at a transcriptional level. 56,57 Moreover, activin A is only observed in the cytoplasm of IgE-activated bone marrow-derived murine mast cells, whereas in resting state this cytokine is not detected. 57 Mast cell degranulation is a process that is highly dependent on the induction of cytosolic Ca 2+ .…”
Section: Mast Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to other cytokines, activin A appears to be secreted in a second wave of mediators by mast cells, thus requiring de novo synthesis at a transcriptional level. 56,57 Moreover, activin A is only observed in the cytoplasm of IgE-activated bone marrow-derived murine mast cells, whereas in resting state this cytokine is not detected. 57 Mast cell degranulation is a process that is highly dependent on the induction of cytosolic Ca 2+ .…”
Section: Mast Cellsmentioning
confidence: 99%
“…56,57 Moreover, activin A is only observed in the cytoplasm of IgE-activated bone marrow-derived murine mast cells, whereas in resting state this cytokine is not detected. 57 Mast cell degranulation is a process that is highly dependent on the induction of cytosolic Ca 2+ . Similarly, the release of activin A is also dependent on the activation of the Ca 2+ -calmodulin-dependent enzymes, calcineurin and CamK, which synergize with p38 mitogenactivated protein kinase and c-Jun NH 2 -terminal kinase activity to further regulate activin bA subunit transcription.…”
Section: Mast Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that activin can both have an inhibitory or proliferative effect on cell proliferation; dependent on the cell type (41)(42)(43)(44)(45)(46)(47). In vivo studies have shown that FST knockout mice died soon after birth due to a variety of skeletal and cutaneous defects amongst other defects seen in the activin-deficient mice (48).…”
Section: Abstract Follistatin (Fst) As a Single-chain Glycosylated mentioning
confidence: 99%
“…Inflammatory stimuli seem to induce the production of activin A by various cell types, including peritoneal macrophages (28), monocytes (29), mast cells (30), or Th2 cells (27,31). Indeed, activin A is released into the circulation as early as 1 h after LPS injection (32,33).…”
mentioning
confidence: 99%